Global phylogenomics of multidrug-resistant Salmonella enterica serotype Kentucky ST198. Issue 7 (20th May 2019) - Hawkey, Jane; Le Hello, Simon; Doublet, Benoît; Granier, Sophie A.; Hendriksen, Rene S.; Fricke, W. Florian; Ceyssens, Pieter-Jan; Gomart, Camille; Billman-Jacobe, Helen; Holt, Kathryn E.; Weill, François-Xavier
Abstract : Salmonella enterica serotype Kentucky can be a common causative agent of salmonellosis, usually associated with consumption of contaminated poultry. Antimicrobial resistance (AMR) to multiple drugs, including ciprofloxacin, is an emerging problem within this serotype. We used whole-genome sequencing (WGS) to investigate the phylogenetic structure and AMR content of 121 S. e nterica serotype Kentucky sequence type 198 isolates from five continents. Population structure was inferred using phylogenomic analysis and whole genomes were compared to investigate changes in gene content, with a focus on acquired AMR genes. Our analysis showed that multidrug-resistant (MDR) S. enterica serotype Kentucky isolates belonged to a single lineage, which we estimate emerged circa 1989 following the acquisition of the AMR-associated Salmonella genomic island (SGI) 1 (variant SGI1-K) conferring resistance to ampicillin, streptomycin, gentamicin, sulfamethoxazole and tetracycline. Phylogeographical analysis indicates this clone emerged in Egypt before disseminating into Northern, Southern and Western Africa, then to the Middle East, Asia and the European Union. The MDR clone has since accumulated various substitution mutations in the quinolone-resistance-determining regions (QRDRs) of DNA gyrase ( gyrA ) and DNA topoisomerase IV ( parC ), such that most strains carry three QRDR mutations which together confer resistance to ciprofloxacin. The majority of AMR genes in the S . e nterica serotype Kentucky genomes were carried either on plasmids or SGI structures. Remarkably, each genome of the MDR clone carried a different SGI1-K derivative structure; this variation could be attributed to IS 26 -mediated insertions and deletions, which appear to have hampered previous attempts to trace the clone's evolution using sub-WGS resolution approaches. Several different AMR plasmids were also identified, encoding resistance to chloramphenicol, third-generation cephalosporins, carbapenems and/or azithromycin. These results indicate that most MDR S . e nterica serotype Kentucky circulating globally result from the clonal expansion of a single lineage that acquired chromosomal AMR genes 30 years ago, and has continued to diversify and accumulate additional resistances to last-line oral antimicrobials. This article contains data hosted by Microreact .